INTERNATIONAL EXPERIENCE IN ENHANCING THE EFFECTIVENESS OF PRELIMINARY INVESTIGATION AND INQUIRY PROCEEDINGS - Pardayev, Elbek (Journal of Fundamental Studies, 2026)
The article examines foreign experience in improving the conduct of preliminary investigation and inquiry in order to identify mechanisms applicable in the Republic of Uzbekistan. Based on a comparative legal analysis, it considers models for organizing pre-trial proceedings in the Russian Federation, the Republic of Kazakhstan, the Republic of Belarus, the Federal Republic of Germany, the French Republic, and the United States of America. The study identifies the principal areas for reforming investigative activity: the institutional separation of the powers of investigation and prosecution, the strengthening of judicial oversight, the reduction of procedural workload for investigators, the development of departmental specialization, the introduction of the institution of the investigator’s assistant, the improvement of employees’ social protection, and the use of automated systems for the allocation of criminal cases. It is established that the greatest effectiveness is demonstrated by a comprehensive approach combining organizational, legal, and technological measures. The article concludes that the use of foreign experience may contribute to enhancing the efficiency, objectivity, and transparency of preliminary investigation, as well as strengthening the procedural independence of the investigator within the national criminal procedure system.